Comportamento estrutural de pilares armados e não armados, construídos com blocos de terra compactados - Borja, Rômulo Thomaz de Figueiredo (2019)
Compacted Earth Block (CEB) construction uses technology that converts the earth into structure, bringing the simplicity of the natural soil supply along with adequate standards of strength and durability. The flexibility of load bearing masonry design allows for various building styles, from traditional walls to pillars and arches. The objective of this work was to analyze the structural behavior of reinforced and non reinforced CEB columns subjected to centered loading. The blocks were characterized by axial compression and absorption tests. Three types of columns were made and characterized by the axial compression test, rupture mode analysis, displacements and cracking in the structural element. It was observed that the reinforced CEB columns performed better when compared to the non reinforced ones. However, block crushing was the main cause for the structural collapse of all columns. Finally, we conclude that we cannot consider the design model proposed by NBR 15812 (2010) for ceramic block masonry columns, as a representative model for CEB columns.